Implications of unprofitable horizontal mergers: A positive external effect does not suffice to clear a merger! - Oliver Budzinski; Jürgen-Peter Kretschmer (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2009)
We demonstrate that the popular Farrell-Shapiro-framework (FSF) for the analysis of mergers in oligopolies relies regarding its policy conclusions sensitively on the assumption that rational agents will only propose privately profitable mergers. If this assumption held, a positive external effect of a proposed merger would represent a sufficient condition to allow the merger. However, the empirical picture on mergers and acquisitions reveals a significant share of unprofitable mergers and economic theory, moreover, demonstrates that privately unprofitable mergers can be the result of rational action. Therefore, we extend the FSF by explicitly allowing for unprofitable mergers to occur with some frequency. This exerts a considerable impact on merger policy conclusions: while several insights of the original FSF are corroborated (f.i. efficiency defence), a positive external effect does not represent a sufficient condition for the allowance of a merger anymore. Applying such a rule would cause a considerable amount of false positives.
Keywords: L13; L41; K21; D43; 330; oligopoly theory; horizontal merger policy; profitability of mergers; antitrust; Fusion; Konzentrationspolitik; Oligopol; Theorie